2010
DOI: 10.1123/mcj.14.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedforward Control in Human Locomotion During Avoidance of Obstacles that Change Size

Abstract: The purpose of the current study was to understand how visual information about an ongoing change in obstacle size is used during obstacle avoidance for both lead and trail limbs. Participants were required to walk in a dark room and to step over an obstacle edged with a special tape visible in the dark. The obstacle's dimensions were manipulated one step before obstacle clearance by increasing or decreasing its size. Two increasing and two decreasing obstacle conditions were combined with seven control static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
3
3
0
1
Order By: Relevance
“…This ability to use visual information for trailing limb control has already been suggested for a static obstacle avoidance situation when vision was manipulated during planning and approach [6]. In addition, Santos et al [11] showed this in a more dynamic situation for changing obstacle heights at a trailing limb foot contact (similar timing to T1 in the present study). However, previous studies involved only modifying an already planned trailing limb strategy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This ability to use visual information for trailing limb control has already been suggested for a static obstacle avoidance situation when vision was manipulated during planning and approach [6]. In addition, Santos et al [11] showed this in a more dynamic situation for changing obstacle heights at a trailing limb foot contact (similar timing to T1 in the present study). However, previous studies involved only modifying an already planned trailing limb strategy.…”
Section: Discussionsupporting
confidence: 86%
“…This further supports independent control between limbs [6,8,12]. It appears that the previously suggested feedforward influence of leading limb function on trailing limb control [11] is thus context specific and likely only true when both limbs perform the same ALA (i.e., both stepping over an obstacle).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…No changes in foot placement were observed, suggesting that the position cue provided salient online information to guide foot placement. This finding agrees with previous research that reported that humans control the obstacle crossing task guiding the leading limb on a feedforward manner using visual information (Moraes, Lewis, & Patla, 2004;Santos, Moraes, & Patla, 2010).…”
Section: Research Articlesupporting
confidence: 93%
“…In numerous studies a large variety of configurations of obstacles, their locations, and timings of their presentation during walking on walkways and treadmill belts have been used to analyze how humans avoid obstacles (Bauby and Kuo 2000;Berard and Vallis 2006;Chen et al 1991Chen et al , 1994Chou et al 2001;Mohagheghi et al 2004;Moraes et al 2004Moraes et al , 2007Owings and Grabiner 2004;Patla et al 1989Patla et al , 1999Patla and Rietdyk 1993;Santos et al 2010;Warren et al 1986;Weerdesteyn et al 2005;Zijlstra et al 1995). These studies showed that humans adapt their strategies for avoiding obstacles according to the context of the experimental task.…”
mentioning
confidence: 99%